Effects of Vitamin D supplementation on 8-hydroxydeoxy guanosine and 3-nitrotyrosine in patients with type 2 diabetes: a randomized clinical trial - Damghanian, Parisa; Javanbakht, Mohammad Hassan; Mohammadzadeh Honarvar, Niyaz; Yousefirad, Esmaeil; Mohammadi, Hamed; Zarei, Mahnaz; Djalalli, Mahmoud (Progress in Nutrition, 2019)
Objective: This study was done to assess the effects of vitamin D supplementation on oxidative stress biomarker in p patients with Type 2 Diabetes Mellitus (T2DM). Methods: This randomized double-blind clinical trial was done with 35 type 2 diabetic participants. The vitamin D group (n= 17) and the placebo group (n= 18) were stratified for BMI and age at the baseline before random allocation. The vitamin D group received 4000 IU (100µg) vitamin D3/day whereas the placebo group received matching placebo. The effect of vitamin D3 on 8-OHdG and 3- nitrotyrosine was measured by ELIZA kit at the beginning and at the end of the study. Results: After two months supplementation, the mean concentration of serum 8-OHDG had significantly decreased (P=0.015) in vitamin D group. The mean concentration of 3-NT decreased in both groups, whereas this reduction was significant only in vitamin D group (p=0.027). Conclusions: Vitamin D supplementation at the dose of 100µg for 2 months had beneficial effects on oxidative stress T2DM management. Results from this trial showed that there were beneficial effects associated with the use of vitamin D supplementation,specifically reducing 8-OHDG and 3-NT concentrations.